Pertanggungjawaban Korporasi terhadap Pencemaran Lingkungan Hidup : Studi Pada Pt Horizon Bandar Bahru di Batam - Tantimin Tantimin (Fakultas Hukum, Universitas Internasional Batam, 2017)
Development that affects the environment, such as pollution and / or damage to the environment, which has a wide and very dangerous impact on people's lives. Such as Buyat Bay Pollution Case, Lapindo Mud Case in Sidoarjo, Illegal Logging Case Adelin Lis in Medan, Case of Imported Waste from Australia, Mud Waste Import Case from Singapore for reclamation of Pelambung Bay and Nipah Island, and Case of Import of Hazardous and Toxic Waste (B3 ) from the